Role of Ultrasound in the Diagnosis and Management of Gall Bladder Diseases (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: The majority of published data on the sensitivity and specificity of ultrasound (US) in the diagnosis of gallbladder pathology was conducted over 30 years ago. Since then the quality and resolution of ultrasonography has improved significantly. It is, therefore, essential to asses afresh whether the progression in technology has translated into improved diagnostic accuracy. The present study was undertaken to find the usefulness of US in diagnosing gallbladder diseases with particular reference to cholecystitis and gall bladder carcinoma.Methods: This cross-sectional observational study was conducted at the Department of Radiology and Imaging, Rajshahi Medical College, Rajshahi in collaboration with the Departments of General Surgery and Histopathology of the same Medical College between July 2016 to June 2018. A total of 128 patients were initially included on the basis of signs and symptoms of gallbladder diseases. All these patients were subjected to abdominal US to achieve a ultrasonic diagnosis of gall bladder disease followed by histopathological examination of biopsy material taken from the gall bladder or specimen of the operated gall bladder. The accuracy of ultrasound in the diagnosis of gall bladder diseases was determined by comparing the ultrasound sound diagnosis with that of histopathological diagnosis. In particular, the role of ultrasound was evaluated in the differentiation of benign gall bladder diseases from those of malignant ones.Result: Age distribution of the patients shows that over one-third (35.9%) was ≥50 years old followed by 24.9% 40-50 years, 21.9% 30 - 40 years and 16.4% 20 – 30 years old with mean age of the patients being 43.8(range: 18-80) years. Females outnumbered males by roughly 11:9. In terms of BMI, 6.2% were underweight, 16.4% overweight, and 4.7% obese. The predominant complaints reported by the patients were pain in the right upper abdomen (95.3%), epigastric pain (94.7%), abdominal discomfort (96.9%) followed by nausea (75%), low-grade fever (37.5%), jaundice (26.6%) and vomiting (26.6%). Approximately 44% of the patients exhibited anaemia. Nearly half (46.1%) of the patients exhibited sonographic Murphy’s sign. Hyperechoic echo character was invariably obtained with 12.5% cases having hypoechoeic character as well. Over 90% of the patients had gall-stones, 62.5% cholecystitis (thickened gall-bladder wall). Ultrasound comment on the type of diseases revealed that 112(87.5%) were benign diseases and 16(12.5%) malignant cases. Approximately 55% of the gall bladder diseases diagnosed by histopathology were cholecystitis. Histopathological comment shows that about 90% of the diseases were benign and the rest (10.2%) were malignant. The sensitivity of ultrasound in diagnosing cholecystitis was 85.9%, while the specificity of the test was 60.9% with overall diagnostic accuracy of the test being 73.4%. The US had a optimum sensitivity (84.6%) and high specificity (95.6%) in diagnosing gall-bladder carcinoma.Conclusion: The study concluded that US could be considered as the preferred initial imaging technique for patients who are clinically suspected of having acute calculous cholecystitis. It is also a useful imaging modality for diagnosing gall-bladder malignancy. Thus, US can be dependably used in the primary evaluation of heptobilliary pathology.Ibrahim Card Med J 2017; 7 (1&2): 70-75